Stability Model Prediction Using the Response Surface Approach to Assess the Outcomes of Vitamin B12 Injection Post-Market Sampling - Yulia Yulia; Sri Hartati Yuliani (Sanata Dharma University, 2024)
B12 injections are one of the most widely used vitamins in Indonesia. The nature of vitamin B12, which is easily degraded by environmental factors, has been widely reported. This research aimed to determine the effect of stability optimization model predictions with post-market sampling of vitamin B12 injection preparations by considering the variables of temperature, humidity, and distribution time. Factorial design was used to determine the stability optimization model. Validation of the analysis method using ultraviolet (UV) spectrophotometry showed valid results for testing. Stable product outcomes were seen during the research period based on the results of post-market sampling, optimization of stability conditions by evaluating pH parameters, and content determination. Post-market sampling data showed a pH decrease of 3.46% in the Palembang distribution area and an increase in pH of 4.54% and 5.33% in the Cirebon and Denpasar distribution areas. In the Palembang distribution area, the content of cyanocobalamin decreased by 0.90%, while in the Cirebon distribution area, it decreased by 0.94%. A paired t test for statistical analysis was used to determine the significance of the model. The results obtained show that there was no significant difference between the prediction model and the results of post-market sampling (p-values of 0.065 and 0.491) or H0 received